Biodeterioration should be controlled properly for efficient and sustainable forest products (woods) utilization. This research aimed to know the distribution of wood biodeterioration in house structure; the biodeterioration intensity and its economic loss in Lembang, Bogor, Serang and North Jakarta, which were different in temperature and humidity. The survey was conducted to 200 houses in the four places. The result showed that wood biodeterioration occured in most (90%) house buildings. Do - Trisna PRIADI; Dodi NANDIKA; Kurnia SOFYAN; ACHMAD .; Arif Budi WITARTO (Departemen Hasil Hutan, IPB, 2010)
Biodeterioration should be controlled properly for efficient and sustainable forest products (woods) utilization. This research aimed to know the distribution of wood biodeterioration in house structure; the biodeterioration intensity and its economic loss in Lembang, Bogor, Serang and North Jakarta, which were different in temperature and humidity. The survey was conducted to 200 houses in the four places. The result showed that wood biodeterioration occured in most (90%) house buildings. Doors, windows and roof structures were the most frequent attacked by biodeterioration agents. Decay fungi attacked wet wooden house components, mainly lisplank and ceiling, whereas termites attacked mainly doors, windows, poles and walls. The volume of damaged wooden house components in Lembang and Bogor were higher than those in the warmer and drier regions, Serang and North Jakarta. The average economic loss due to wood biodeterioration in a houses was about Rp28 000/year. However the economic loss per region was quite high, about two billion rupiahs per year in Serang and more than eight billion rupiahs in Bogor City. Keywords : Biodeterioration, decay fungi, termites, beetles, residential buildings